O risco com um pé no chão ou a cabeça no ar : o H2020 enquanto oportunidade para evitar o risco de desconforto bioclimático em espaços urbanos - Monteiro, Ana (2016)
The European Union (EU) has chosen to adapt to climate risks as an explicit priority in its 2020 strategy. However, it is common to conclude that this concern should focus mainly on the increased frequency of extreme heat events since it is predicted a time of global warming. However, the analysis of intra- and inter-annual behaviour of temperature and of social and economic vulnerabilities in Europe's southern countries advises a focus also in cold extreme events. The combined daily analysis of temperature rhythm and mortality (all causes) and morbidity from stroke attacks in the Oporto area confirms the relevance of this approach and highlights the serious negative impacts that cold days had, between 2002 and 2007, in human beings. And it is very important to note that the resistance thresholds to cold are, in the Southern countries of Europe, much higher than those usually considered by decision-makers.